INTERFERENCE IN LEARNING ENGLISH: GRAMMATICAL ERRORS IN ENGLISH ESSAY WRITING AMONG SEVENTH GRADERS OF MTs DARUL ULUM, SUKOSEWU, BOJONEGORO, EAST JAVA - Ghufron, M. Ali (English Teaching Journal, 2015)
The purpose of this research was to present an analysis of interference effect, a factor that plays an important role in inhibiting the acquisition of English among seventh grade students of MTs Darul Ulum, Sukosewu, Bojonegoro, East Java. The data substantiating the discussion throughout this article came from an empirical study of errors in essays written by seventh grade students of MTs Darul Ulum in the academic year of 2015/2016. The participants were all students in 7A class consisting of 30 students. The participants were chosen by cluster random sampling. The findings of the study show that the learners are still having difficulty in using correct English grammar in their writings. The three most frequent errors are: 1) the use of articles, 2) subject-verb agreement, and 3) copula âbeâ.